Gambaran Pola Hidup Pasien Gagal Jantung Kongestif Paska Rawat di RSUD dr. Slamet Garut - Devi Ratnasari; Hasbi Taobah Ramdani; Wildansyah Wildansyah (Jurnal Medika Cendikia, 2017)
People life style with congestive heart failure is influeneed by many factors. This is important to be noticed to meet the needs of the body’s metabolism. The porpuse of this research was to know the life style of congestive heart failure patients under out patient in RSUD dr. Slamet Garut 2016. Reserch methods used was a deskritive and the variable was patient’s life style. The population was whole of congestive heart failure patient. Using a purposive sampling method of the number of samples was 97 responden. The results shawed that most responden ( 54,6%) have a good life style, the majority of the respondents (54,6%) did activity/sport routine, almost all the respondents (79,4%) controlled their nutritional intake, most of respondents (75,3%) folowed the treatment, and almost all of respondents (80,4%) not smoke. It was expeeted to increase health promotion about healthy life style of activity/sports, nutritional intake, adherence to therapy and smoking about disease congestive heart failure.